High-Sensitive Troponin-T as a Predictive Outcome Factor in COVID-19 Hospitalised Patients: Analysis After One-Year Follow-Up - Stojanović, Darko; Ćetojević, Živko; Dujaković, Boris; Stanetić, Mirko; Kovačević-Preradović, Tamara; Stanetić, Bojan (Scripta Medica, 2021)
Introduction: Since December 2019, the humanity is constantly under affection of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Despite global dissemination, neither the treatment or the specific predictive factors have been found or strictly defined yet. Aim: Aim of this study was to assess the long-term (1 year) predictive value of high-sensitive Troponin T (hsTnT) in COVID-19 affected, hospitalised patients. Methods: Between 5 March 2020 and 31 March 2020, 87 consecutive patients hospitalised at University Clinical Centre of the Republic of Srpska due to SARS-CoV2-caused pneumonia, in whom hsTnT was measured, were included. The Kaplan-Meier analysis was used to assess differences in all-cause mortality between the groups. Independent predictors of all-cause mortality were identified through univariate- and multivariate Cox regression analysis. Results: Compared with patients who had normal hsTnT levels, patients with raised hsTnT were significantly older (70.7 ± 13.23 vs 49 ± 15.29; p < 0.001). Glucose values were significantly increased in patients with raised hsTnT (9.29 ± 5.14 vs 6.76 ± 2.46 [4.1-5.9] mmol/L; p = 0.005), as well as serum creatinine (179.07 ± 225.58 vs 87.53 ± 18.16 µmol/L; p = 0.01), hsTnT (187.43 ± 387.29 vs 7.58 ± 3.40 pg/mL; p = 0.003), D-dimer (5.94 ± 13.78 vs 1.04 ± 1.26 [0-0.50] mg/L; p = 0.024), C-reactive protein (125.92 ± 116.82 vs 69.97 ± 73.09) [< 5.0] mg/L; p = 0.009) and calcium (1.32 ± 0.46 vs 1.03 ± 0.173 [2.20-2.65] mmol/L; p = 0.001). Kaplan-Meier analysis revealed that the number of all-cause deaths at 1 year was 19 of whom 18 were presented with elevated hsTnT (log-rank p < 0.001). When univariate Cox regression was applied, multiple predictors of all-cause mortality have been identified ie age, haemoglobin, haematocrit, urea, CK-MB as well as hsTnT. In a multiple regression model, hsTnT remained an independent predictor of poor outcome. Conclusion: Results from this study showed that the value of hsTnT during hospitalisation is possibly associated with long-term poor outcome of COVID-19 patients. Therefore, hsTnT may appear as a surrogate factor to differentiate between patients at high risk who need more intensive follow-ups.